Analysis of genotoxic effects on plants exposed to high traffic volume in urban crossing intersections. (November 2020) - Campos, Carlos Fernando; Cunha, Matheus Campos; Vieira Santos, Vanessa Santana; Olegário de Campos Júnior, Edimar; Bonetti, Ana Maria; Pereira, Boscolli Barbosa
Abstract: A biological assessment of environmental quality was performed using the tropical plant species Tradescantia pallida (Rose) D.R. Hunt. var. purpurea exposed to different levels of air contamination in urban intersections with high volume of vehicle traffic. Air quality (average daily levels of particulate material in the PM1, 2.5, 10 fractions) and traffic volume in crossing intersections were monitored for 30 days before the collection of plants. Frequency of micronuclei and pollen abortivity in inflorescences collected at different intersections with gradual levels of traffic volume were evaluated as biomarkers of genotoxicity. In addition, the concentrations of bioaccumulated heavy metals in the leaves of the collected plants were also investigated. The proposed biological assessment model found a positive association between the environmental variables (traffic volume; concentration of particulate material) and biological effects (leaf concentration of Cr and Cd; micronucleus frequencies and pollen abortivity). Graphical abstract: Image 1 Highlights: Environmental assessment using biomarkers is appropriate to monitor early effects. Validation of an in situ plant exposure in urban crossing intersections was conducted. Frequency of micronuclei and pollen abortivity in Tradescantia pallida were evaluated. Concentrations of bioaccumulated heavy metals in the plant were also investigated. Biological responses were correlated to traffic volume and particulate material levels.